2011
DOI: 10.1128/jvi.02108-10
|View full text |Cite
|
Sign up to set email alerts
|

Export of Adenoviral Late mRNA from the Nucleus Requires the Nxf1/Tap Export Receptor

Abstract: One important function of the human adenovirus E1B 55-kDa protein is induction of selective nuclear export of viral late mRNAs. This protein interacts with the viral E4 Orf6 and four cellular proteins to form an infected-cell-specific E3 ubiquitin ligase. The assembly of this enzyme is required for efficient viral late mRNA export, but neither the relevant substrates nor the cellular pathway that exports viral late mRNAs has been identified. We therefore examined the effects on viral late gene expression of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 90 publications
(139 reference statements)
1
25
0
Order By: Relevance
“…Our recent RNA chromatin immunoprecipitation assays suggest that agnoprotein is an RNA binding protein (data not shown) rather than a DNA binding protein (75). As mentioned above, we believe that dimeric and oligomeric forms of agnoprotein may play important roles in the transport of JCV transcripts from the nucleus to the cytoplasm in a Crm1-dependent (72,73) or -independent (76) manner. This possibility will be further investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Our recent RNA chromatin immunoprecipitation assays suggest that agnoprotein is an RNA binding protein (data not shown) rather than a DNA binding protein (75). As mentioned above, we believe that dimeric and oligomeric forms of agnoprotein may play important roles in the transport of JCV transcripts from the nucleus to the cytoplasm in a Crm1-dependent (72,73) or -independent (76) manner. This possibility will be further investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, its interaction with the HAdV-C5 E4 Orf6 protein has been reported to promote cytoplasmic accumulation of ARE-containing mRNAs via an XPO1-independent pathway (Higashino et al, 2005). The selective export of viral late mRNAs is also XPOl independent (Flint et al, 2005; Yatherajam et al, 2011) and requires the E4 Orf6 protein (Blanchette et al, 2008; Woo and Berk, 2007) raising the possibility that ANP32A might participate in regulation of mRNA export in HAdV-C5-infected cells. We therefore investigated the effect of RNAi-mediated inhibition of ANP32A synthesis on viral late gene expression, by monitoring the accumulation of the late protein, protein V (Berk, 2013), as it is well established that the impaired export of viral late mRNAs in cells infected by E1B 55 kDa-null mutant viruses leads to substantial defects in late protein synthesis (Babiss et al, 1985; Harada and Berk, 1999; Pilder et al, 1986; Williams et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Selective export of viral late mRNAs requires formation of the E1B 55 kDa protein-containing E3 ubiquitin ligase (Blanchette et al, 2008; Woo and Berk, 2007) and the major cellular mRNA export receptor NXF1 (Yatherajam et al, 2011), but the relevant substrate(s) of the virus-specific ligase have not been identified. The NXF1 receptor is not targeted for proteasomal degradation in HAdV-C5-infected cells, nor are two subunits (THOC1 and THOC4) of the TREX complex (Yatherajam et al, 2011), which couples export to prior reactions in mRNA biogenesis (Katahira, 2012; Reed and Cheng, 2005). One class of proteins enriched in the E1B 55 kDa protein-associated population is defined by the GO term RNA splicing (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Since during Ad replication the transport of bulk cellular mRNA is simultaneously blocked (193,194), it is likely that one or more proteins implicated in their export are targeted for proteasomal degradation, which might, in turn, promote preferential export of viral transcripts. Second, further studies suggested that the cellular export receptor of bulk cellular mRNA, TAP/NXF1, participates in the export of Ad late transcripts (195). An interesting hypothesis is that cellular export factors are relocalized to viral transcription and replication centers and thus promote efficient export of newly transcribed mRNAs out of the nucleus.…”
Section: Nuclear Dna Virus Replication Centersmentioning
confidence: 99%